Overview of Changes in Blood Pressure and PulsOverview of Changes in Blood Pressure and Pulse in Spinal Anesthesia Sectio Caesarea Patients at Banjarnegara Islamic Hospitale in Spinal Anesthesia Sectio Caesarea Patients at Banjarnegara Islamic Hospital - Rahmannisa, Putri Haifa; Sebayang, Septian Mixrova; Wibowo, Tophan Heri; Suandika, Made (Java Nursing Journal, 2023)
Background: Hypotension is one of the complications that often occurs after induction of spinal anesthesia. This study aims to determine changes in blood pressure and pulse spinal anesthesia in sectio caesarea patients at Banjarnegara Islamic Hospital. Methods: This study used descriptive quantitative method with cross-sectional approach. This research was conducted in June 2023. The research sample was 44 respondents. The sampling technique was purposive sampling. This research instrument is by observing and recording the results of observations to the research observation sheet and matching observation data with medical records. Results: The results of this analysis showed a change in blood pressure and pulse, namely a decrease in blood pressure in the 15th minute on Systolic Blood Pressure as many as 17 people (38.6%) and Diastolic Blood Pressure as many as 15 people (34.1%). The pulse frequency before induction was predominantly normal as many as 36 respondents (81.8%) and when giving spinal anesthesia induction increased at minute 0 as many as 27 people (61.4%). Conclusion: blood pressure and pulse have changes when given spinal induction of anesthesia.